Behavioral strategies in conflict among adolescents with different levels of anxiety - Novikova, Kseniya Vladimirovna; Tkach, Elena Nikolaevna (Психолог, 2025)
The subject of the study is the examination of conflict behavior strategies in adolescents with different levels of anxiety. The object of the study is the conflict as a socio-psychological phenomenon. The authors note that the issue of anxiety's influence on adolescents' behavior in conflict situations occupies an important place in psychology; anxiety significantly affects adolescents' learning success, as well as their relationships with teachers, parents, and peers. The authors examine existing theoretical perspectives on the concept of anxiety in both foreign and domestic research, the features of anxiety manifestations in adolescence, the essence of behavior strategies in conflict situations, and the results of empirical research on conflict behavior strategies in adolescents with varying levels of anxiety. Special attention is given to describing differences in conflict behavior strategies among adolescents with different levels of anxiety. Empirical research methods include diagnostic techniques: the Spielberger-Hanin Scale of Trait and State Anxiety; the "Multidimensional Assessment of Children's Anxiety" by E.E. Romitsyn; the "Strategies for Behavior in Conflict Situations" by L.K. Kazantsev; and the Thomas-Kilmann Methodology. Statistical processing methods applied include the Shapiro-Wilk test, Spearman's correlation analysis, Fisher's ANOVA, and Tukey's exploratory method. The theoretical significance and novelty of the research lie in the analysis and systematization of theoretical perspectives regarding the features of strategy selection in conflicts among adolescents with different anxiety levels. The authors demonstrate that there are differences in conflict behavior strategies among adolescents with varying levels of anxiety. Adolescents with high anxiety levels are characterized by avoidance and accommodation strategies in conflict. Adolescents with moderate anxiety adopt a compromise strategy. Those with low anxiety levels more frequently use collaboration and competition strategies. The obtained data have important practical implications, enabling the development of psychological support programs for adolescents aimed at reducing high anxiety levels and forming constructive behavior models in conflict situations. The research results may be useful for educators, psychologists, and parents in constructing effective interaction strategies with adolescents prone to elevated anxiety. The findings could serve as a basis for developing practical recommendations for adolescents.